Edgeworth Equilibria - Aliprantis, C. D.; Brown, D. J.; Burkinshaw, O. (Econometrica, 1987)
This paper studies pure exchange economies with infinite dimensional commodity spacces in the setting of Riesz dual systems. An Edgeworth equilibrium is an allocation that belongs to the core of every replication of the ec onomy. Under some mild conditions, it is shown that (1) Edgeworth equ ilibria exist, (2) an allocation is an Edgeworth equilibrium if and o nly if it is an approximate quasiequilibrium, and (3) if preferences are uniformly proper, then every Edgeworth equilibrium is a quasiequi librium. The obtained results specialize to most exchange economies t hat have appeared in the literature of general equilib rium theory. Copyright 1987 by The Econometric Society.